2018
DOI: 10.3389/fmicb.2018.00615
|View full text |Cite
|
Sign up to set email alerts
|

Effective Biodegradation of Mycotoxin Patulin by Porcine Pancreatic Lipase

Abstract: Patulin is a common contaminant in fruits and vegetables, which is difficult to remove. In this study, the biodegradation of patulin using porcine pancreatic lipase (PPL) was investigated. The method of HPLC was used to analyze the concentration of patulin. Batch degradation experiments were performed to illustrate the effect of PPL amount, pH, temperature, contact time, and initial concentration. Besides, the degradation product of patulin was characterized by full wavelength scanning and MS technologies. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The procedure has shown appreciable performance when applied under pH 6.0 conditions, for 42 hr, and at a temperature of 40°C (Li et al., 2017). A different activity was observed by Liu, Peng, and Meng (2018), who found that PPL can degrade above 90% of PAT in aqueous solution at pH 7.5, 40°C for 48 hr and identified the residual product as C 7 H 11 O 4 + . In apple juice, the degradation rate of PAT was greater than 70% from an initial level of 1 × 10 3 µg/L.…”
Section: Current Application Of Biotechnology In the Face Of The Foodmentioning
confidence: 76%
“…The procedure has shown appreciable performance when applied under pH 6.0 conditions, for 42 hr, and at a temperature of 40°C (Li et al., 2017). A different activity was observed by Liu, Peng, and Meng (2018), who found that PPL can degrade above 90% of PAT in aqueous solution at pH 7.5, 40°C for 48 hr and identified the residual product as C 7 H 11 O 4 + . In apple juice, the degradation rate of PAT was greater than 70% from an initial level of 1 × 10 3 µg/L.…”
Section: Current Application Of Biotechnology In the Face Of The Foodmentioning
confidence: 76%
“…Fruit juices and purees may contain PAT. Enzymatic degradation of PAT has been associated with different species of bacteria and yeast [ 196 ]. The Fum8p enzyme produced by Aspergillus welwitschiae has the ability to detoxify fumonisins and produce less toxic compounds (FPy and Fla), including those produced by Fusarium spp.…”
Section: Mitigation Policies Of Mycotoxin Contamination In Beveragesmentioning
confidence: 99%
“…This phenomenon was primarily caused by more drastic motions of the molecules in the system under higher temperatures which increased the chances of contact of PAT with yeast cells, and thus enhanced PAT adsorption rate. On the other hand, the metabolic activity of yeast cells would also be increased with temperature (Kannamba et al 2010;Liu et al 2018).…”
Section: Effects Of Different Fermented Conditions On Patremoving-capacity By Yeast Cellsmentioning
confidence: 99%